Supplementation of Protected Sodium Butyrate Alone or in Combination With Essential Oils Modulated the Cecal Microbiota of Broiler Chickens Challenged With Coccidia and Clostridium perfringens - Bortoluzzi, Cristiano; Rothrock, Michael James; Vieira, Bruno Serpa; Mallo, Juan Jose; Puyalto, Monica; Hofacre, Charles; Applegate, Todd Jay (Frontiers in Sustainable Food Systems, 2018)
The objective of this study was to determine the effects of protected sodium butyrate (SB), and protected sodium butyrate plus essential oils (carvacrol and ginger; SBEO) on the cecal microbiota of broilers challenged with Eimeria maxima and Clostridium perfringens. Birds were assigned to 4 treatments (8 replicates pens of 58 birds/pen): unchallenged control; challenged control; challenged and supplemented with SB; challenged and supplemented with SBEO. On d 13, challenged birds were orally inoculated with 5,000 Eimeria maxima oocysts. On d 18-19, the same birds were exposed to Clostridium perfringens via drinking water ( 8 log CFU/ml). Cecal excreta was collected at d 12, 18, 21, and 28 for microbiome analysis through 16s rRNA sequencing using Illumina MiSeq platform and analyzed using QIIME v. 1.9.1 The cecal microbiota was analyzed over time within each experimental group. The inclusion of SB alone or in combination with EO contributed to larger variations in the cecal microbiota over time than the unsupplemented treatments, as shown by the diversity indices. The community structure and abundance of the cecal microbiota were significantly different across ages, especially in the groups supplemented with SB and SBEO. As shown in the PCoA analysis, the supplementation of SB led to a more stable microbial community and lower between-sample variability over time. In the unchallenged control birds, Ruminococcus decreased (p = 0.006), whereas Bacteroides and Clostridiales increased (p ≤ 0.02) as the birds aged. In the challenged control group, however, the frequency of Coprococcus and Blautia decreased as birds aged (p ≤ 0.01), and, Clostridiales did not increase. Supplementation of SB, but not SBEO, increased the frequency of Lactobacillus (p = 0.01) on d 12 compared to d 18 and d 28, and prevented the reduction in the frequency of Blautia as the birds aged. Nevertheless, supplementation of SB and SBEO contributed to unique changes in the predicted functions of the cecal microbiota over time, which was not observed in the unsupplemented birds. SB and SBEO modulated the diversity, composition, and predictive function of the cecal microbiota which may have lowered the negative impact of necrotic enteritis (NE).